(untitled) (Global Journal of Human-Social Science, 2019)
The study mapped the behaviours and traits of the youths who have participated in political base violence. It was a triangulated study that adopted a longitudinal survey approach. The study interviewed 160 participants and was guided by the Utilitarian Theory of Rational Choice. Data were collected using a culturally specific 14-item instrument designed and validated by the researchers. Data were analysed using SPSS complimented with Narrative Latent Content Analysis. Findings from the study submit that violence exposure results in different risks of mental distress-disorders. Bases in Zimbabwe have affected the youths psychologically and behaviourally.